Exchange rate risks and asset prices in a small open economy - Alexis Derviz (European Central Bank (ECB), 2004)
The paper proposes a multi-factor international asset pricing model in which the exchange rate is allowed to be co-determined by a risk factor imperfectly correlated to other priced risks in the economy. The significance of this factor can be established as long as one is able to observe a proxy for the foreign cash order flow. Then, the asset pricing model is decomposed into the standard ICCAPM no-arbitrage setup characterized by a pricing kernel, in which, however, the “autarky” exchange rate is unobserved, and an additional equation that links this autarchic currency price with the FX order flow. The model is put in the state space form. The unobserved variables span the macroeconomic risk factors with an impact on the asset markets and determine the dynamics of the pricing kernel, the autarchic exchange rate and the FX order flow. A comparison of models allowing for an independent OF risk factor with a restricted one, where the forex order flow plays no role, should disclose the existence of a “nonfundamental” source of a systematic divergence of the observed and the autarchic (i.e. fundamental) FX returns. The model is calibrated and tested on the Czech koruna/euro exchange rate in a setting with seven Czech and euro area asset returns.
Keywords: F31; F41; G12; G15; 330; exchange rate; latent risk; order flow; pricing kernel; state space